Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Pemecahan Masalah Siswa pada Materi Laju Reaksi di SMA Negeri 7 Gorontalo - Fitria Lamalani; Netty Ino Ischak; Masrid Pikoli (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students’ problem-solving abilities in the reaction rate material at SMA Negeri 07 Gorontalo. The research employed a quasi-experimental method with a pretest-posttest control group design. The subjects consisted of two classes: class XI1 as the experimental group (using the PBL model) and class XI2 as the control group (using conventional learning). The instrument used was an essay test based on problem-solving indicators. The results showed a significant improvement in problem-solving ability in the experimental class compared to the control class. The average posttest score of the experimental class was 74 (categorized as good), while the control class scored 52 (categorized as fair). The t-test results indicated a significant difference between the two groups (p < 0.05), suggesting that the PBL model is more effective in enhancing students' problem-solving abilities than conventional learning methods.